Heart-minds and harquebuses: the Bozhou rebellion in China (1587-1600) - Noordam, Barend (Small wars & insurgencies, 2022)
Many of the non-Chinese minorities inhabiting the south-western regions of the Ming empire (1368-1644) rebelled during the course of the dynasty’s existence, including the Miao, who at the end of the sixteenth century launched an uprising under the leadership of Yang Yinglong (1551-1600). The uprising and the resulting insurgency were eventually suppressed under the leadership of two civil officials, Guo Zizhang (1543-1618) and Li Hualong (1554-1611). During the early dynasty forceful suppression by the military together with the generous offering of amnesties and rewards to induce peaceful surrender had constituted the strategy for dealing with minority insurgencies. In contrast, civil officials, like Neo-Confucian thinker Wang Yangming (1472-1529), conceptualized mixed policies emphasizing moral exhortations and social engineering, in combination with military force using advanced technologies, as integrated solutions to the problem in the course of the sixteenth century. This paper will look at the extent to which these mixed policies were advocated and applied, and their relative measures of success.
Gesehen am 16.01.2026